Sikap Bahasa pada Lanskap Linguistik Papan Nama Penginapan di Kampung Prawirotaman Yogyakarta - Nurshaleh Ma’aruffyan Yusuf; Frans Asisi Datang (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
Linguistic landscapes generally function as a source of information regarding patterns of language use in a region. However, Linguistic Landscape is not just a presentation of linguistic facts, but also describes the language identity of a region. This research aims to analyze language attitudes that are manifested on inn or hotel signboards in Prawirotaman. The data used in this research comes from documentation and interviews taken directly at each hotel in Prawirotaman. Using a qualitative approach, this research focuses on analyzing language attitudes, which include fidelity in language use, pride in language use, and awareness of the correct use of grammar. The qualitative analysis method considers linguistic and contextual aspects inherent in hotel or lodging signage data. The findings show that the analysis of language attitudes in the linguistic landscape shows a less than optimal level of loyalty and pride towards the use of Indonesian, while the use of grammar is considered quite proficient. The lack of pride and loyalty towards Indonesians may be due to the prevalence of the use of English, which is considered more easily recognized by foreign tourists and visitors.